1997
DOI: 10.1093/humrep/12.4.827
|View full text |Cite
|
Sign up to set email alerts
|

Age of the uterus does not affect pregnancy or implantation rates; a study of egg donation in women of different ages sharing oocytes from the same donor

Abstract: The importance of age of the recipient (uterine age) with regards to pregnancy rate, delivery rate and miscarriage rate following oocyte donation was evaluated using retrospective data analysis of cases where two recipients from different age groups shared oocytes from a single donor and had equal numbers of embryos transferred. A total of 104 women (21-52 years of age) underwent a total of 104 cycles of oocyte donation. They were divided into groups according to age (group A: age 39 years or less and group B:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 8 publications
3
28
0
2
Order By: Relevance
“…They concluded that capacity to conceive and maintained a gestation when oocyte quality is controlled appears to be independent of uterine age. Using the same model, Abdalla et al [27] reported similar pregnancy and miscarriage rate when recipients were younger or older than 39 years, concluding that decline in fertility with age can not be explained by uterine factors alone. Noyes et al [28] found, using five age groups (<35, 35-39, 40-44, >45), that recipient age does not adversely affect pregnancy potential.…”
Section: Discussionmentioning
confidence: 98%
“…They concluded that capacity to conceive and maintained a gestation when oocyte quality is controlled appears to be independent of uterine age. Using the same model, Abdalla et al [27] reported similar pregnancy and miscarriage rate when recipients were younger or older than 39 years, concluding that decline in fertility with age can not be explained by uterine factors alone. Noyes et al [28] found, using five age groups (<35, 35-39, 40-44, >45), that recipient age does not adversely affect pregnancy potential.…”
Section: Discussionmentioning
confidence: 98%
“…In other instances, eggs may be procured from patients undergoing in vitro fertilization (IVF) who anonymously share oocytes with recipient couples in exchange for discounted or free IVF services [5]. Other programs provide oocytes aspirated from a single donor and 'split' among two or more recipients [6].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies are of matched case-control design analyzing recipient outcome with sibling oocytes from the same donor (15)(16)(17)(18). To our knowledge there are only three published studies (19)(20)(21) analyzing several recipient factors (demographic and cycle data, male factor, and ET difficulty) at the same time in oocyte recipients with a discordant outcome, but these studies reach divergent conclusions.…”
mentioning
confidence: 99%